Power cycling tests under driving ΔTj = 125 °C on the Cu clip bonded EV power module. (November 2022) - Kim, Dongjin; Lee, Byeongsoo; Lee, Tae-Ik; Noh, Seungjun; Choe, Chanyang; Park, Semin; Kim, Min-Su
Abstract: This study investigated the power cycling performance on a transfer-molded power module with Cu clip bonding for the next-generation green automotive applications. A 700 V/900A class 2-in-1 half bridge power module was designed and fabricated by using Cu clip bonding and transfer-molding technologies. The switching was precisely controlled so that ton was 0.5 s and toff was 4.5 s by a constant current mode. The condition of the power cycling tests (PCTs) was ∆ T = 125 °C with the maximum repetition of 97, 000 cycles. The performance and life of the power module was evaluated based on AQG-324, and thermal resistance of the junction (Rth-ja ) was monitored during PCTs. The major failure in this investigation was increase in the thermal resistance (Rth ). Microstructural integrity of the interconnections were characterized in detail by scanning acoustic tomography (SAT) and interfacial microstructure analysis using a scanning electron microscopy (SEM). The degradation mechanism of the interfacial material was numerically revealed through finite element method (FEM) simulations. Highlights: Power cycling performance of transfer-molded power module with Cu clip bonding was investigated. Reliability test of A 700V/900A class 2-in-1 half bridge power module was conducted with Tjmax = 175 °C and Tc = 50 °C. Increase in thermal resistance induced by IMC growth and crack propagation of the chip was main cause of module failure.